Spatial Transformation of Physical Change of Built-up Land in Ambon City Center, Indonesia, Period 1940-2025 - Rifai, Ahmat; Rakuasa, Heinrich; Halim; Latue , Philia Christi; Sarfan , Riri; Tehupelasury, Syifa (Asian Journal of Environmental Research, 2025)
The background of this research focuses on the physical transformation of built-up land in the center of Ambon City from 1940 to 2025, influenced by historical, social, and economic factors, including the impact of riots and population growth. The tools and materials used in this research include thematic maps of land use from various periods, satellite images (Ikonos-2 and Planet Scope), and ArcGIS Pro software for spatial data processing. The method applied is an urban morphology approach with qualitative deductive analysis, which includes geospatial data processing to understand the pattern of urban development. The results of the discussion show that built-up land has increased significantly, although environmental challenges remain a major concern, such as the conversion of green land that impacts the carrying capacity of the environment. The conclusion of this study emphasizes the need for sustainable urban planning strategies to balance urban growth with ecosystem preservation in the future.